2020
DOI: 10.3390/pr8050582
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Parallel Robotic Cultivations with Online Multivariate Analysis

Abstract: In conditional microbial screening, a limited number of candidate strains are tested at different conditions searching for the optimal operation strategy in production (e.g., temperature and pH shifts, media composition as well as feeding and induction strategies). To achieve this, cultivation volumes of >10 mL and advanced control schemes are required to allow appropriate sampling and analyses. Operations become even more complex when the analytical methods are integrated into the robot facility. Among oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…In spite of such difficulties, some trials to operate SeqBR, or cyclic BR, or even parallel BR have been reported in the literature, by using two to five biological FBR [40][41][42], 14 cyclic BR [43], 48 parallel BRs [44], or 24 parallel BRs [45]. As expected, optimized FBR reported better performances compared to the simple BR due to a higher operating flexibility [5,15,22,46].…”
Section: The Choice Of N Brmentioning
confidence: 87%
“…In spite of such difficulties, some trials to operate SeqBR, or cyclic BR, or even parallel BR have been reported in the literature, by using two to five biological FBR [40][41][42], 14 cyclic BR [43], 48 parallel BRs [44], or 24 parallel BRs [45]. As expected, optimized FBR reported better performances compared to the simple BR due to a higher operating flexibility [5,15,22,46].…”
Section: The Choice Of N Brmentioning
confidence: 87%
“…Another very important application in bioprocessing is smart operations of parallel high-throughput experimental systems. Here such digital twins can efficiently learn across all of the ongoing operations and reduce (in real-time) the redundant information, while consistently redesigning the experiments to provide further knowledge. , In such cases, experimental systems and digital twins must actively collaborate on simultaneously improving process understanding as well as the process itself.…”
Section: The Crystal Ball: Digital Twinsmentioning
confidence: 99%
“…The recent development of high-throughput (HT) technology allows for performing a large number of laborious and time-consuming experiments by automatizing, parallelizing, and miniaturizing the experimental facilities (Puskeiler et al, 2005;Bunzel et al, 2018;Hemmerich et al, 2018). Liquid handling stations support the parallel cultivation on a large numbers of mini-bioreactors, based on the automated sampling, on-line and at-line analytics operation, real-time control, and data acquisition (Kusterer et al, 2008;Tai et al, 2015;Haby et al, 2019;Hans et al, 2020b). HT technology plays an important role especially in the early stage bioprocess development.…”
Section: Introductionmentioning
confidence: 99%